ORGANIZATIONAL COMPETENCIES OF THE LOCAL SELF-GOVERNMENT OFFICIALS IN UKRAINE: THEORETICAL PRINCIPLES OF THE RESEARCH - Dzeha, Volodymyr (Theory and Practice of Public Administration, 2019)
Professionalism is one of the most important directions in the development of representative power in the conditions of Ukraine's integration into the European space. The main scientific approaches to the definition of the concept of competence and competencies are considered in paper. The definition of "organizational competence of local self-government officials" and the basic organizational competencies and ways of their improvement are given by the author. The role of competences of local self-government officials acquires a special theoretical and socio-practical significance at the present stage of socio-economic and political development of the state in the conditions of global challenges. It is caused by the reform of all sectors of public life and the peculiarities of the decentralization reform, which requires professionalism from the subjects of the representative government in Ukraine.However, despite the large number of works by native and foreign scholars, the issue of improving the organizational competence of local self-government officials, the development of effective technologies for the formation of basic organizational competences of local self-government officials remains unexplored. Moreover, even there is no definition of "organizational competence", although such a term is used to determine the structure of professional competencies.The purpose of the research is to identify and systematize directions and ways of improving the organizational competences of local self-government officials in the context of reforming public administration. The main scientific approaches to the definition of the concept of competence and competencies are considered in paper. The subject of our research is the organizational competence of local self-government officials which does not have a definition. Therefore, the definition of the organizational competence of local self-government officials is scientifically substantiated and in demand practically. Based on the content of the initial concepts of "competence" and "organize" the author's definition of the concept of "organizational competence" is formulated.Organizational competencies are a set of knowledge, skills and knowledge in collecting and analyzing information, making policy and management decisions, communicating and peculiarities of working with people, resolving conflicts, the ultimate goal of which is to solve the operational and strategic tasks of professional activity effectively with the mobilization of the necessary resources, in number of human ones. Among these skills we consider the most urgent: communicative competence, since the role of communications in modern society is steadily increasing, and mobilizing people to achieve certain goals without the exchange of information is simply not possible; possession of technologies for policy-management decisions, since officials of any level have to make many strategic, tactical and operational decisions, the quality of which depends on the fate of many people; competence in conflict management, since conflict is the natural property of socio-political relations, and in the context of large-scale political reforms, the innovation conflict is permanent and requires constant response and adjustment of the behavior of the participant-parties. Consequently, the high level of the demand for politico-managerial practice, which is constantly being transformed and modernized, dictates the need for a theoretical substantiation of problems that need to be resolved.